2021
DOI: 10.3390/en14123478
|View full text |Cite
|
Sign up to set email alerts
|

Study on Boil-off Gas (BOG) Minimization and Recovery Strategies from Actual Baseload LNG Export Terminal: Towards Sustainable LNG Chains

Abstract: Boil-off Gas (BOG) generated at the liquefied natural gas (LNG) export terminal causes negative economic and environmental impacts. Thus, the objective of this study is to develop and evaluate various handling schemes to minimize and/or recover the generated BOG from an actual baseload LNG export terminal with a capacity of 554 million standard cubic feet per day (MMSCFD) of natural gas feed. The following three main scenarios were assessed: JBOG re-liquefaction, LNG sub-cooling, and lean fuel gas (LFG) reflux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Bouabidiet al, [26] presented a study on analysis of the processes in the components of the LPG (propane/ butane) re-liquefaction plant under the conditions of co-mingling in tanks when transporting by sea. In the analysis, energy analysis of the mixture-based reliquefaction plant has been performed using the monitoring data of an LPG cargo operation.…”
Section: Overview Of Lpg Processes and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Bouabidiet al, [26] presented a study on analysis of the processes in the components of the LPG (propane/ butane) re-liquefaction plant under the conditions of co-mingling in tanks when transporting by sea. In the analysis, energy analysis of the mixture-based reliquefaction plant has been performed using the monitoring data of an LPG cargo operation.…”
Section: Overview Of Lpg Processes and Storagementioning
confidence: 99%
“…While the growing LPG adoption rate undoubtedly holds huge promise for Nigeria's clean energy agenda (due to LPG's low carbon intensity) Nigeria does not appear to be ready for large-scale LPG adoption in its domestic market. This un-readiness is due to a number of bottlenecks including a low level of regulation of the LPG retail market, shortage of LPG facilities, an unresolved tank crisis in the country, and BOG generation in the LPG storage tank [26].…”
Section: Domestic Consumption and Retail Marketing Of Lpgmentioning
confidence: 99%
“…Even though BOG reliquefication increases LNG output, it needs power. While the industry has long been using the NG feed as a fuel, systematic integration of all fuel gases including BOG (e.g., tank and jetty) is useful to reduce power consumption. Hence, as argued by Bouabidi et al, balancing BOG and other gas generation with a plant’s FG needs is important to ensure that the LNG plant is sustainable in terms of energy requirements and emissions . Second, the present literature ignores key process/equipment/product specifications, such as the high heating value (HHV) of the LNG product, the NGL Reid vapor pressure (RVP), and the WI/pressure of FG.…”
Section: Introductionmentioning
confidence: 99%
“…16−18 Hence, as argued by Bouabidi et al, balancing BOG and other gas generation with a plant's FG needs is important to ensure that the LNG plant is sustainable in terms of energy requirements and emissions. 19 Second, the present literature ignores key process/equipment/product specifications, such as the high heating value (HHV) of the LNG product, the NGL Reid vapor pressure (RVP), and the WI/pressure of FG. Most gas turbines mandate a certain minimum pressure and WI of FG.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Results indicated that the attainable excess LNG flow ranged from 0.02 to 0.07 million tonne per annum (MTA). The preliminary economic assessment revealed profits ranging from $7.63 to $24.58 million …”
Section: Introductionmentioning
confidence: 99%